2015
DOI: 10.1186/s13021-015-0036-3
|View full text |Cite
|
Sign up to set email alerts
|

Climate change mitigation effect of harvested wood products in regions of Japan

Abstract: BackgroundHarvested wood products (HWPs) mitigate climate change through carbon storage, material substitution, and energy substitution. We construct a model to assess the overall climate change mitigation effect (comprising the carbon storage, material substitution, and energy substitution effects) resulting from HWPs in regions of Japan. The model allows for projections to 2050 based on future scenarios relating to the domestic forestry industry, HWP use, and energy use.ResultsUsing the production approach, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 30 publications
0
25
0
1
Order By: Relevance
“…The IPCC [42] noted that wood products mitigate GHG emission because they represent carbon storage sources and low carbon energy sources and generate material substitution effects. Kayo et al [43] estimated the climate change mitigation effect of harvested wood products in Japan and clarified that material and energy substitution effects have considerable potential to reduce GHG emissions in Japan. In material substitution processes, cellulose nanofiber technology improves the quality of wood-based material for building and manufacturing products [44].…”
Section: Resultsmentioning
confidence: 99%
“…The IPCC [42] noted that wood products mitigate GHG emission because they represent carbon storage sources and low carbon energy sources and generate material substitution effects. Kayo et al [43] estimated the climate change mitigation effect of harvested wood products in Japan and clarified that material and energy substitution effects have considerable potential to reduce GHG emissions in Japan. In material substitution processes, cellulose nanofiber technology improves the quality of wood-based material for building and manufacturing products [44].…”
Section: Resultsmentioning
confidence: 99%
“…The wood flow and stock targeted in this study are shown in figure . The details of the wood MFA were previously described by Kayo and colleagues (, ). We analyzed the wood flow from log production to lumber (including glued laminated lumber and laminated veneer lumber), plywood (including wood‐based panels such as particle board and fiberboard), chip production, and final consumption of wood and paper products for building construction (lumber and plywood), civil engineering (logs and lumber), furniture (lumber and plywood), and paper and paperboard (chips).…”
Section: Methods and Datamentioning
confidence: 99%
“…We used the following three future scenarios for the period of 2014–2050: baseline, moderate increase (of wood consumption), and rapid increase (of wood consumption), according to the methodology of Matsumoto and colleagues () and Kayo and colleagues (). The main indicators used in the scenarios are shown in table .…”
Section: Methods and Datamentioning
confidence: 99%
“…During the solution process, a MOO model is first reformulated as single objective problems and solved to obtain the Step 1: This step mimics the process where harvesting operations at the TSC are conducted without consideration for residue utilization at the BSC. First, the TSC MOO model is solved with objective functions to maximize NR TSC and NS TSC (Equations (19) and (20)), subject to constraints in Equations (5)-(7), (17), (18) and (21)- (24). NR TSC and NS TSC are not the final TSC net revenues and net GHG emission savings.…”
Section: Solution Proceduresmentioning
confidence: 99%
“…Replacing non-renewable resource processing with less energy-intensive manufacturing necessary to produce wood products is another benefit to using dead beetle-killed wood [17,18]. Timber products can also serve as carbon storage while in use [19], can substitute fossil fuels as energy feedstock [20], or continue to preserve carbon in the landfill at the end of its service life [21].…”
Section: Introductionmentioning
confidence: 99%